Analisis Manfaat dan Pentingnya Microsoft Word bagi Semua Kalangan - Nailan Ni’mah Sinaga; Nurhadiah Nurhadiah; Nurlaila Hasibuan; Rizka Salsabila; Nurbaiti Nurbaiti (Universitas Muhammadiyah Enrekang, 2022)
This study aims to explain how important Microsoft Word is for everyone. This research was compiled after collecting some Microsoft Word information and theories, in other words, this research is classified as an information-based qualitative method.With the results obtained, namely, understanding and history of Microsoft Word and its development, functions and benefits for the field of work or education. Ms. Office Word is a fairly professional word processing software, introduced and created by Microsoft Corporation aimed at various Operating Systems, such as DOS, Apple Macintosh, SCO Unix, OS/2, and Microsoft Window. In history (history), Ms. Word was first introduced to the public on the twenty-fifth of October 1983, but did not use the name Ms. Word as we know it today but with the name Multi-Tool Word, since then,, Ms. Word is constantly evolving. Until now, the word processing software application has been ranked number one in the world of word processing. Causing the necessity to understand this simple application. from the field of education to work or office, Microsoft Office Word plays an important role in making it easier for someone to do their work. So, among the pace of technology that is believed to continue to grow, we are expected to be able to master Microsoft Word and realize how important this application is to implement.